Investigation on the Influence of the Bit Radius and Impact Velocity on Rock Fragmentation by Discrete Element Method - Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The bit–rock interaction is a key point in the fracture process observed in excavation applications, which makes its analysis relevant. As the discrete element method (DEM) has been successfully applied to study rock breakage behavior, we apply it in the present study to analyze various aspects of the bit–rock interaction. This research focuses on numerically analyzing the bit–rock interaction, encompassing the force penetration relationship (FPR), mechanical energy transfer to the rock, and the efficiency of the mechanical energy transfer process. In order to perform this analysis, we simulate various bit radii and impact velocities. In this study, we establish a power–law function to describe the relationship between the energy transferred to the rock and the force, both as functions of bit penetration. The least-squares method is employed to accomplish this determination. Remarkably, it was observed that the latter aligns with the Hertzian contact law when lower impact velocities of the bit are employed. Moreover, a bit-radius-dependent optimal velocity for the mechanical energy transfer process was determined, signifying its significance in the design of excavation tools. The primary conclusion drawn from this research is the quantification of the influence of both the bit impact velocity and the bit radius on the force penetration relationship during the bit–rock interaction. This quantification was achieved by employing the coefficients derived from the regression model established for the FPR. These findings hold practical implications for the enhancement of excavation tools’ efficiency during the design phase, thus contributing to advancements in the field of excavation engineering. © 2023 by the authors.
Keywords: discrete element method; rock mechanics; bit-rock interaction; force-penetration relationship; indentation; button bit